Älgens barkgnag på granstammar : omfattning med avseende på geografisk utbredning, skadad volym och ekonomiska konsekvenser - Steffen, Helena (SLU/Southern Swedish Forest Research Centre, 2008)
In three areas in the province of Småland studies has been done to investigate how big damage the moose may do to P. abies. An inquiry examination and two different types of surveys were done to find out how big area, which volume and which financial consequences the moose debarking has had on the forest. When the volume was calculated the rot spreading was included. The area that was damaged was stipulated with the answers from the inquiry examination. 59 % of the asked forest owners answered the inquiry. The area that the study included was on 22 900 ha and the result showed that there were moose damages on 162 ha. When the whole trees were included the damaged volume was 16 m3sk/ha which is 8, 6 %. On the damaged 162 ha totally 2 570 m3sk was damaged, 385 m3sk had technical damages and 616 m3sk had damages which included decayed wood. When the financial calculation was made only the first 3 meters was included, this because the assumption was done that the decaying wood never extended above 3 meters. The damaged volume counted on 3 meters was 4, 3 m3sk/ha, totally 692 m3sk. If a comparison is made between timber prices and pulpwood prices the difference is 67 000 kr, all areas included.